Nipped in the bud: mesograzer feeding preference contributes to kelp decline. Issue 7 (1st July 2016) - O'Brien, John M.; Scheibling, Robert E.
Abstract: Small invertebrate grazers can disproportionately reduce plant fitness by discriminately consuming valuable tissues, but the context and attendant consequences of this activity at higher levels of ecological organization rarely are considered. To assess the impact of a gastropod mesograzer Lacuna vincta on fecundity and potential reproductive output of the habitat‐forming kelp Saccharina latissima, we measured the intensity and distribution of grazing damage on kelp blades at five sites of varying kelp density, during the annual reproductive peak (October–November) in Nova Scotia. We found most grazing damage on reproductive individuals consisted of superficial excavations, and was concentrated on the central sorus (region where sporangia develop) compared to the vegetative blade margins. Grazing intensity on sori (percent grazed) averaged 29.6% across sites and sampling periods. The distribution of grazing on non‐reproductive individuals was opposite to that of reproductive ones, indicating that snails shift feeding from blade margins to the center as sori develop. Choice and no‐choice feeding assays in the laboratory revealed that focused grazing on sori is likely due to an active feeding preference for sporogenous over vegetative tissue. This preference was correlated with the distribution of chemical defense between tissues (phlorotannin content was 2.5 times higher in vegetative tissue than sori), but not nutritional quality (no difference in C/N ratio). We deduce, with support from histological observations, that consumption of sorus tissue by L. vincta reduces fecundity of S. latissima . Extrapolating our results to estimate potential reproductive output within kelp beds suggests that spore supply and recruitment limitation may be predominantly imposed by the scarcity of reproductive individuals in the most degraded kelp beds. However, loss of reproductive output to grazing could extend recruitment limitations that impede recovery of waning kelp populations in Nova Scotia.